Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas - heikal muhammad zakaria hakim; Gusganda Suria Manda; Arif Rakhman (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
Abstract- This study aims to determine the effect of cash turnover and accounts receivable turnover on profitability (ROA) in cosmetics and household needs companies listed on the Indonesia Stock Exchange in the period 2011-2016. The independent variables in this study are cash turnover and accounts receivable turnover. For the dependent variable in this study is profitability (ROA). The population taken in this study were cosmetics and household needs companies listed on the Indonesia Stock Exchange during the period of 2011 - 2016. The sampling technique used was purposive sampling technique and obtained a sample of 5 companies. the type of data used is secondary data taken by the method of documentation and literature study. The data analysis technique used is multiple linear regression analysis, classic assumption test and hypothesis test using t test. The results of the partial hypothesis test show that there is a significant positive effect between cash turnover on profitability (ROA) and there is a significant positive effect between accounts receivable turnover to profitability (ROA). Keywords: Cash Turnover, Receivable Turnover, Profitability (ROA)